Kebenaran Ilmiah - Risal Qori Amarullah (Edusifa: Jurnal Pendidikan Islam, 2025)
Truth is an eternal question for humans in every basic age; truth is that which exists or does not exist. Truth is only possible when something exists. The truth is very important, but the issue of the truth is very relative, because maybe today it is true, but tomorrow it may not be true. Therefore, in finding the truth, this paper will reveal the criteria for determining that everything that exists can be categorized as true. closely related to the qualitative approach. The descriptive analytic method is an as-is description that comes from a place or character who is the perpetrator of an event; it can also come from a character whose thoughts are involved by collecting data from literature related to discussions about the meaning, theory, and nature of scientific truth. The results of this study are: The meaning of scientific truth is a state that is correct, in accordance with things or conditions that actually exist and really exist, and is true if these truths are the truths taught by religion. Theories of truth consist of correspondence theory, coherence theory, pragmatic theory, and performative theory. The nature of scientific truth consists of three characteristics, namely: a rational and logical structure, which is empirical, and the last is pragmatic.